What is the hidden curriculum, and how does it affect nursing students? - Meducator, The; Farquharson, Simon; Nguyen, Laura (The Meducator, 2019)
The hidden curriculum can be defined as that which is taught to students unintentionally by the culture, structure, and people of their educational setting. Although most authors agree on its importance, little is written about how the hidden curriculum affects nursing students in both university and clinical placements. The purpose of this review is to take a broad look at the research on the hidden curriculum in an attempt to better understand its current value and future potential, as it affects nursing students and the profession. A brief history of the hidden curriculum is provided in relation to nursing education, followed by a review of the literature with a specific focus on the variety of educational and clinical applications in which it plays important roles. These topics arose from interactions with peers, nurses, non-faculty staff, and other community members, all of which had potential impacts on the students. Ultimately, the hidden curriculum is an understudied, underappreciated component of education, and is one in which students play a major personal role in developing. Both faculty and students need to understand the power and importance of this tool, as it has the capacity to shape the future of the nursing profession.